Analysis of Microbial Community Structure and Diversity in Burial Soil of Yangguanzhai Cemetery - Wei, Xiaoyang; Ling, Xue; Yang, Liping; Zhang, Jun; Cui, Menghe; He, Zhang; Zhao, Xichen; Sun, Manli (Frontiers in Microbiology, 2022)
As one of the common physical remains in archaeological discoveries, human bones are important bases for studying the history of human development, which is of great significance for exploring the evolution law of ancient human, reconstructing ancient human society, and tracking the development of human civilization. However, in the process of human bone burial, in addition to being affected by physical and chemical factors, it will also be affected by microorganisms in the buried soil, resulting in a variety of diseases. According to the determination and analysis of the microbial community structure and diversity in the burial soil of Yangguanzhai Site in Gaoling District in Xi'an city, Shaanxi Province, this paper attempts to explore the influence of microorganisms in the burial environment on human bones, in order to provide scientific proof for the microbial prevention and control of bone relics in the archaeological excavation site. For the first time, Illumina Novaseq high-throughput sequencing technology was used to analyze the microbial community structure in the burial soil. At the phylum level, there were 8 dominant bacteria species in the soil samples of tombs, which were Firmicutes, Actinobacteriota, Actinobacteria, Proteobacteria, Acidobacteriota, Methylomirabilota, Chloroflexi, Bacteroidota. At the genus level, there were 12 dominant species in the soil samples of tombs, including MIZ17, MND1, Gaiella, oc32, Kroppenstedtia, Halomonas, Bacteroides, Dongia, Faecalibacterium, Nocardioides, Pseudomonas, Pseudonocardia. The overall microorganisms in the soil of Yangguanzhai Cemetery were relatively well-distributed, and the microbial community structure near human bones is the most abundant and diverse. Therefore, it is necessary to take some measures to control microorganisms and protect human bones.